The Role of Law in Strengthening Democratic Governance - Rifa’i, Iman Jalaludin; Abdullah, Abdullah (Journal of Law and Social Politics, 2025)
Democratic governance is fundamentally upheld by the rule of law, which ensures transparency, accountability, and citizen participation. However, in many jurisdictions, weak legal frameworks, judicial inefficiencies, and political interference hinder the effectiveness of democratic institutions. Strengthening the legal framework is crucial for sustaining democracy and preventing authoritarian tendencies. This research analyzes the role of law in reinforcing democratic governance by examining legal principles, institutional mechanisms, and case studies from various democratic nations. It identifies key legal elements that contribute to a stable and effective democracy. This research employs a qualitative approach, utilizing doctrinal legal analysis and comparative case studies. Legal documents, judicial decisions, and governance reports are analyzed to assess the impact of legal frameworks on democratic governance. The findings indicate that robust legal systems, independent judiciaries, and strong constitutional safeguards are pivotal in promoting democratic governance. Countries with well-established legal protections for civil liberties and checks on executive power tend to exhibit greater political stability and public trust. Conversely, weak legal systems often correlate with corruption, electoral fraud, and democratic backsliding. Strengthening the rule of law is essential for sustaining democracy. A well-functioning legal system safeguards human rights, ensures governmental accountability, and enhances public participation in governance. This research contributes to legal and political scholarship by providing a framework for assessing the effectiveness of legal systems in democratic governance. It offers insights for policymakers and legal scholars on how legal reforms can strengthen democratic institutions globally.